The Francovich Principle as the Basis of State Responsibility for Laborer Loss Due to Company Bankruptcy - Widyantoro, Agus; Taufiqurrohman, Moch. Marsa; Nugraha, Xavier (Yustisia, 2023)
The absence of legal certainty in the application of the pari passu pro rata parte principle in the distribution of bankrupt accounts in Indonesia has given rise to uncertainty regarding the protection of the rights of laborers whose employers or companies have faced bankruptcy. This article considers that Indonesia requires a set of formulations enabling the state to provide legal protection for the rights of laborers affected by employer or company bankruptcy. The article explores the feasibility of adopting the Francovich Principle in Indonesia, defining it as a principle holding the state accountable for the losses incurred by laborers due to company bankruptcies.  The  article  concludes  that  several  conditions must be met to apply the Francovich Principle, including the establishment of a guarantee institution, the obligation for financial contributions from companies, and the implementation of specific measures to prevent abuse. The state’s effort to adopt the Francovich Principle involves establishing a priority scale in drafting laws related to the Francovich Principle into the Priority National Legislation Program. Furthermore, the government needs to revitalize institutions related to the Francovich Principle within the national legal and regulatory system